(3NGdUI GdMbGFbs - (3GdaGQjGHj, eMehO Hf CMeO Hf CHj GdMSjf, J(B607(3g`s
(3ChdgG (B:s
(3jbhd GdYHO GdZQjb aj ZeQGJ CdhGf GdYUjGf eMehO Hf CMeO GdaGQjGHj JGH Gddg Ydjg hZaQ dhGdOjg LeYJ HJhajb Gddg NGdb GdfSe hQGRb GdbSe Ld LdGdg hYe fhGdgcJGH NGdUI GdMbGFb hfUGH ZGjJg GdObGFb ef fja hSHYjf UMjaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 161s
(3eYLe GdeDdajf(B: 3 / 794s
(3cTa GdXfhf(B: 1 / 699s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs